Anthropogenic factors of PM2.5 distributions in China's major urban agglomerations: A spatial-temporal analysis. (10th August 2020) - Liu, Xiangping; Zou, Bin; Feng, Huihui; Liu, Ning; Zhang, Honghui
Abstract: Fine particulate matter (PM2.5 ) poses a severe threat to public health in China. Understanding the PM2.5 distributions and relevant key drivers in major Chinese urban agglomerations by considering both spatial and temporal heterogeneities can provide an insight into formulating effective mitigation policies. In this study, we selected 12 urban agglomerations characterized by high levels of urbanization and severe PM2.5 pollution levels as our study area for the period of 1998–2016. Firstly, the indexes of GDP per capita and industrial structure were utilized to divide urban agglomerations into different urbanization stages. Then, advanced economic panel estimations (including the panel-corrected standard error (PCSE) method and feasible generalized least squares (FGLS) method) were employed to quantify the relationships between five anthropogenic factors and PM2.5 concentrations at the entire urbanization scale and the urbanization stage scale. As the results show, the urbanization processes of the 12 urban agglomerations studied can be classified into four different urbanization stages: the Primary Industrial Stage, Middle Industrial Stage, Late Industrial Stage, and Developed Stage. Averaged PM2.5 concentrations first underwent a rapid increase from the Primary Industrial Stage to Middle Industrial Stage and then decreased in the Late Industrial Stage and Developed Stage for most urban agglomerations. At the entire urbanization scale, GDP per capita (GDPP), population density (PD), and the share of secondary industry (IS) are major determinants of PM2.5 concentrations while the foreign direct investment (FDI) and energy intensity (EI) have a comparatively weaker influence. At the urbanization stage scale, GDPP generally made an initially positive and then negative contribution to PM2.5 concentrations throughout the urbanization process while IS and PD became the two main contributing factors as urban agglomerations entered the Late Industrial Stage and Developed Stage. PD significantly elevated PM2.5 levels in populous urban agglomerations throughout the urbanization stages. FDI and EI exhibit quite spatial heterogeneity across the Chinese urban agglomerations. Through a detailed analysis of the spatio-temporal quantification of PM2.5 distributions and of impacts from their determinants, this work contributes to a more thorough understanding of PM2.5 formation in Chinese key urban agglomerations and provides implications for regional joint prevention and control policies. Graphical abstract: Image 1 Highlights: Chinese key urban agglomerations over 1998–2016 could be classified into four different urbanization stages. The averaged PM2.5 concentration for most urban agglomerations present a trend of rise first and then fall. Anthropogenic impacts presented distinctive spatio-temporal heterogeneities among Chinese urban agglomerations. Factors regarding economy, population, and industrial structure are more influential than FDI and energy intensity.